LEARNING THROUGH PLAYING: DEVELOPMENT OF SOFTWARE ARCHITECT’S SKILLS WITH BUILDING BLOCKS - Ahmad, Sabrina; Kasmuri, Emaliana; Muda, Noor Azilah (2014)
Software Architecture and Design is a course introduced in the curriculum of Computer Science Bachelor Degree. It is a part of the software engineering body of knowledge to instill good practice in software development. The teaching and learning method of delivering competence in a high level abstraction is challenging in way to obtain knowledge appreciation among students. The experience of deploying learning through playing in a tutorial session encourages students’ engagement, focus and appreciation of the teaching and learning process. The knowledge is delivered, experienced and actively discussed among students to discover more. This paper presents the design and implementation of the learning through playing building blocks for the purpose of understanding software architect’s roles and responsibilities. The analysis based on the observation of the conduct is discussed and lessons learnt are elaborated.